Laser Leveling- A tool to increase irrigation efficiency at field level - Rajput, T.B.S; Patel, Neelam; Agrawal, Ghanshyam (Journal of Agricultural Engineering, 2004)
High irrigation efficiencies may be achieved if water is delivered uniformly across the field. Topography index (TI) was used to asseSs the smoothness of the land surface of the selected farmers fields of village Masauta, district Ghaziabad, V.P. during 2002-03. No direct relationship was found between TI and field size, however, earthwork requirement per unit area, for laser leveling was found increasing with increasing field sizes (least for small farmers, and highest in case of large farmers). Application, storage and distribution efficiencies showed a decreasing trend with' increasing values of TI. Laser leveling improved all the three efficiencies (application, storage and distribution) in all the cases; however, the percent enhancement of irrigation efficiencies was found to be higher at higher values of TI. After laser leveling, application, storage and distribution efficiencies increased from 58.85 to 64.4%, 50.6% to 69.5% and 70.3% to 81.5% in the field having TI of 5.8 cm whereas these increased from 32.2% to 67.15 %,30.0% to 66.7% and 38.9% to 78.5% in the field with TI of 26 cm, respectively. Laser leveling increased wheat yields, the increase in yield was however more significant in fields with high TI values, before leveling. (14.6 % increase from the field having TI as 5.8 cm but 32.2 % increase in case of the field haVing TI of 26 cm).